Studying the effects of traits in the genotype of three maize hybrids in Hungary - Nasir Mousavi, Seyed Mohammad; Bodnár, Karina Bianka; Nagy, János (Acta Agraria Debreceniensis, 2019)
In this study, we selected three hybrids (Armagnac, Loupiac, and Sushi) for evaluation of the effect of traits in genotype in Debrecen. In 2017, the total rainfall from May to October was 314 mm in Debrecen, which was 236 mm in the winter period before sowing. The obtained results showed that there was a positive correlation between the weight of the cob maize and the rate of seed/cob, number of rows with number of seeds in column and outer diameter ear with weight of cob and number of rows in grain per ear and the rate of seed / cob; Also, there was a negative correlation between grain weight in ear with seed/cob rate, outer diameter ear and the rate of seed/cob and outer diameter ear with the number of leaves. There was a positive correlation between stem diameter, Seed/cob rate and the number of nodes by GGE biplot. In addition, there are traits of weight of all seeds and outer ear diameter that had the highest effect on average yield. Moreover, the number of seeds per row showed the least effect on the average yield of hybrids.